Parental Alienation Syndrome (Focus on Management) - Rina Krismiati Gani; Royke Tony Kalalo (Jurnal Psikiatri Surabaya, 2020)
Parental Alienation Syndrome (PAS) is a process in which one parent (Aligned Parent) teaches his children to reject or antago- nize other parents (Rejected Parent) which results in disruption to the relationship between children and parents. PAS can be a central issue in child custody disputes and is a form of emotional abuse to children that can disrupt the process of growth and development of children and cause mental disorders in the children's future. Although there are differences of opinion about PAS, the impact can already be seen in children who are in the PAS situation. In severe PAS conditions, disorders in children can occur in the dimensions of behavior, emotions, and cognitive. In the long run, someone who has been exposed to PAS in childhood has a greater likelihood of experiencing depression, anxiety, and decreased quality of life in the future. Given the mag- nitude of the impact caused by PAS, it is necessary to do the management carried out simultaneously by mental health practition- ers, legal professionals and the court. Therapeutic interventions that can be carried out include Multi Model Family Intervention (MMFI), Family Reflections Reunification Program (FRRP), Overcoming Barriers Family Camp (OBFC), Parallel Group Ther- apy, and Family Bridges Workshop. There is no conclusion which intervention is the best. Ultimately, the goal of family therapy is to achieve and maintain healthy parent-child relationships.